- Download PDF
2 Answers | Add Yours
`2y + x = 4x=2y`
To start, express the given as two equations.
EQ1: `2y+x = 4x`
EQ2: `2y = 4x`
Then, let's try to express EQ1 as one variable. To do so, substitute EQ2 to EQ1. So, replace the 2x in EQ1 with 4x.
`2y+x = 4x`
Since all the terms have the x variable, bring them together on one side of the equation.
Then, substitute value of x to either EQ1 or EQ2 and solve for x.
`x = 0` , `2y=4x` `2y=0`
Hence, the solution to the given equation is `x=0` and `y=0` .
The double equation x + 2y = 4 x = 2y can be solved by bifercating it in to two equation:
x+2y = 4x or -3x+2y = 0 ..... (1) and
2y = 4x or y = 2x ...........(2)
substituting the value of y from (2) in (1) we get:
-3x + 2*2x = 0
=> x = 0
substituting the value of x in (2), we get:
y = 0
Solution of x + 2y = 4 x = 2y is x = 0 and y = 0
We’ve answered 324,377 questions. We can answer yours, too.Ask a question